EFL Students’ Cognitive, Creative, and Affective Needs in Creative Writing Courses - Parlindungan Pardede (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2026)
Creative writing (CW) has recently been infused into English as a foreign language (EFL) curricula worldwide. Yet, its implementation remains challenging due to limited knowledge of students’ needs required to design effective CW instructions. This study explored EFL students’ cognitive, affective, creative, and pedagogical needs in CW courses within Indonesian higher education. Adopting a sequential explanatory design, 40 college students participated. Qualitative data obtained from observations was analyzed thematically, while quantitative data collected using a questionnaire was analyzed using descriptive statistics. Later, the two strands were merged through joint displays and narrative integration. The cognitive domain findings showed students' strong ideation strategies knowledge but high needs for practice, strong feedback approval, and deep revision challenges. Findings in creative and affective domains disclosed students' strong creative openness and motivation through publication, together with struggles with divergent thinking and authentic voice. Pedagogical domain findings revealed preference for scaffolded support and a significant need for problem-solving and peer review skills. All domains interact through learning strategies, scaffolds, and dispositions, shaping students' readiness dynamic. Thus, combining creative expression and cognitive strategy improvement while addressing affective and pedagogical needs through complementary customized supports is crucial in CW courses.